Prevalence of mutations in Mycobacterium tuberculosis genes coding resistance to isoniazid and rifampicin in tuberculosis patients from different age groups - T. Yu. Salina; T. I. Morozova (Туберкулез и болезни лёгких)
The objective: to study the prevalence and ranges of mutations in katG, inhA, and ahpC genes coding resistance to isoniazid, and in rpoB gene coding resistance to rifampicin in patients with pulmonary tuberculosis from different age groups. Subjects and methods. 253 patients were examined; based on their age they were divided into 3 groups (Group 1 – from 18 to 30 years, Group 2 – from 31 to 60 years, group 3 – from 61 to 80 years). Biological microchips with TB-Biochip reagent kit (Russia) were used. Results. In Groups 1 and 2, compared to Group 3, mutations were recorded more often simultaneously in katG, inhA, ahpC genes and rpoB genes which meant that multiple drug resistance (MDR) prevailed (32.4 and 36.1% against 13.2%, respectively). In general, mutations in katG gene (including MDR + isolated isoniazid resistance) were also confidently more frequent in Groups 1 and 2 (30.9 and 32.7%) versus Group 3 (10.5%). Similar changes were found in the prevalence of the adverse type of ser 315-> Thr mutation of katG gene, which was registered in 23.5% of cases in Group 1, in 21.8% of cases in Group 2, and in 7.9% – in Group 3. In Group 3, mutations in rpoB gene (including MDR) were less frequently recorded and made 26.5% versus 45.5% in Group 1 and 46.9% in Group 2. There were no confident differences in ranges of mutations in rpoB gene between the examined groups of patients. Thus, a significantly lower level of resistance to isoniazid and rifampicin in elderly and senile tuberculosis patients was found compared to young and middle-aged patients, which was registered at the level of genetic mutations.